Pedagogies of lived experience: The perspectives of people with disabilities on their educational presentations about disability topics - Hughes, Oscar (Disability Studies Quarterly, 2023)
Disability Studies in Education (DSE) scholars have described the importance of centering the lived experiences of disabled people in order to understand the complex and context-specific nature of living with a disability and to advance justice and inclusion for disabled people. Researchers have yet to explore the perspectives of disabled people on the potential significance of learning about disability topics from people with disabilities themselves. For the current qualitative study, I interviewed nine people with disabilities who had delivered presentations on personally relevant disability topics in a college course to examine their perspectives on teaching from their lived experience and on the potential broad impacts of opportunities to learn about disability from disabled people. The participants believed that learning from people with disabilities contributed insider perspectives and meaningful interactions to the study of disability topics. They hoped that their presentations would teach students to recognize the capabilities of people with disabilities and to see them as individuals. They believed that learning about disability from disabled people has the potential to improve access to communication and community participation for disabled people. These findings contribute important implications and directions for future research.